Combined Hydrolysis to Yield Increase of Cellulose and (CNCs), Starting from Agroindustrial Rice Husk Waste in Morelos, Mexico - Ricardo Hernández Pérez; René Salgado Delgado; Alfredo Olarte Paredes; Areli Marlen Salgado Delgado; Beatriz Flores Abarca; Oswaldo E. Silva Astudillo (Journal of Water and Environmental Nanotechnology)
Rice husk (Oryza sativa L.) is considered an agroindustrial waste that requires alternative treatment to prevent it from becoming an environmental contaminant. Some recent reports have been able to produce Nanocellulose (CNCs) with this biomass, although with low yields, after using a complex of endo and exoenzymes. Work aimed to evaluate the previous effect of natural proteolytic enzymes (Bromelain/Papain) to degrade the fibrous structure of rice husk before obtaining Cellulose and for whitening, an alternative with hydrogen peroxide. In combination with subsequent enzymatic hydrolysis the new complex formed by four reagents: D-(+)-Cellobiose, endo-1,4-ꞵ-D glucanase, ꞵ-glucosidase, and Cellobiohydrolase, for the synthesis of Nanocrystals (CNCs). Satisfactory results indicated that it was possible to soften and modify the plant tissue structure, which allowed a final cellulose yield of 56.35%. The hydrolysis with the enzyme complex applied to Cellulose, achieved the obtaining of CNCs between 200-595 nm, after using the four enzymes in complex, with better results when used in a single phase, achieving a final yield of 1.8 -4.2% nanocellulose with process optimization.